Seismic assessment of two masonry Baroque churches damaged by the 2012 Emilia earthquake. (September 2017) - Valente, Marco; Barbieri, Gaia; Biolzi, Luigi
Abstract: The structural assessment of historical buildings is a complex and articulated problem based on different activities. This paper describes the different phases of an integrated approach to obtain an accurate knowledge of the structural damage and seismic performance of two masonry Baroque churches located in Northern Italy and hit by the 2012 Emilia earthquake. The activities involved historical research, laser scanning survey, diagnostic investigation and structural analysis. The historical research, based on the analysis of written documents and historical maps, aimed at understanding previous structural problems and major changes in the structure over the centuries. The geometrical survey of the churches was performed by means of a laser scanner technique in order to very precisely determine the geometry of the two churches. Experimental tests and visual inspections allowed identifying location and extent of cracks, construction techniques, presence of voids and defects in structural masonry walls, as well as some characteristics of masonry. Based on this information, detailed three-dimensional finite element models of the two churches were developed and non-linear dynamic analyses were performed. The numerical simulations led to the determination of damage distribution and the identification of the most vulnerable elements, highlighting the main structural deficiencies of the churches when subjected to different levels of seismic actions. Highlights: Structural damage and seismic performance of two masonry Baroque churches Historical research, geometrical survey, diagnostic investigation, experimental tests and structural analysis Damage survey and crack pattern Determination of damage distribution and identification of the most vulnerable elements through detailed FE models